Challenges and prospects for weed management in Pakistan: A review. (August 2020) - Matloob, Amar; Ehsan Safdar, Muhammad; Abbas, Tasawer; Aslam, Farhena; Khaliq, Abdul; Tanveer, Asif; Rehman, Abdul; Raza Chadhar, Asim
Abstract: Weed management has become increasingly important in the backdrop of sustainable crop production, uncertain climatic patterns and food security concerns in Pakistan. Due to diverse agro-climatic conditions, 267 weed species have been identified to be responsible for causing monetary loss worth 3 billion USD annually. Weed competition for resources, interference with crops, weed-related increased incidence of pests and diseases in different crops, and high management costs incurred in controlling weeds make weed management a critical task for the farmers. Moreover, herbicide resistant weeds, labor shortage, higher wages, weed population shifts, changing climatic optima, unavailability of proper and timely inputs, ever increasing threats of invasive weeds, lack of knowledge and training regarding herbicides, and the poor financial resources of the small land holders are major hurdles towards effective weed management in Pakistan. These multi-dimensional problems need holistic line of action with multi-disciplinary collaboration. Improved knowledge of weed ecology, biology, genetics and molecular biology is essential for developing sustainable weed control practices. Some advances are already commercialized, and others are in the process of development. Advancements like vision guided machines for site-specific weed management, recognition and application modules, development of air inclusion nozzles, nanoherbicides, water based formulations with fewer hydrocarbons, herbicide-resistant transgenic crops, robotics to monitor and spray weeds, decision support systems and predictive modeling can be adopted to foster modern weed management in the country. Various conventional weed management approaches like narrow row spacing, row orientation, increased crop density, use of cover crops, intercropping, development of weed-competitive crop cultivars, and their integration can help reduce herbicide input under a given scenario. There is dire need to establish regional weed research institutes under various cropping systems to carry out strategic and applied research in weed science. Innovative teaching and training practices are needed to tackle complex weed management challenges. Effective linkages between academia-research-industry-extension services could play a pivotal role to reframe technological advancements and legislation and to advocate innovations to the farmers. Capacity building, more research fund allocation, and reorienting educational system seem indispensable. Here, we have presented a broad review to summarize the current state of knowledge about the problems and prospects of sustainable weed management approaches in Pakistan. Advanced weed management approaches keeping in view the local agro-ecological conditions have also been discussed in this review to improve the scientific knowledge so that the discipline gets stronger and more focused than ever before. Highlights: Current knowledge about the problems and prospects of sustainable weed management in Pakistan is summarized. Issues of weed science research and education in Pakistan are highlighted and prioritized. Holistic efforts needed to promote weed science research and education are mentioned.